Every case of bipolar disorder is different. Issue 16 (22nd April 2022) - Pollock, Michael
Abstract : America is in the midst of a stealth epidemic. Mood disorders affect more than 21 million Americans and account for over 50% of the nation's suicides every year. What's more, mood disorders cost businesses at least $23 billion annually in lost productivity.